The Nature of Philosophy of Science - Dyah Qotrunnada; Maspuroh; Elsa Nurmalasari; Ilham Mubarok; Mohammad Abdul Al Halib (Penerbit Hellow Pustaka, 2025)
The philosophy of science is a fundamental study of the nature of knowledge, how it is acquired, and its validity and limitations. This study encompasses questions regarding the scientific method, truth, objectivity, and the relationship between theory and reality. In this context, the philosophy of science serves to provide a deeper understanding of the fundamental principles underlying the scientific process and how knowledge is applied. This article explores various philosophical perspectives on science and examines how different approaches influence the development of scientific knowledge across disciplines.